2022
DOI: 10.24251/hicss.2022.524
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Personality Cues for Conversational Agents

Abstract: Conversational agents (CAs)-software systems emulating conversations with humans through natural language-reshape our communication environment. As CAs have been widely used for applications requiring human-like interactions, a key goal in information systems (IS) research and practice is to be able to create CAs that exhibit a particular personality. However, existing research on CA personality is scattered across different fields and researchers and practitioners face difficulty in understanding the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Qiu & Benbast (2009) found that anthropomorphizing bots improves social presence, trust and usage intentions. Ahmad et al (2020) found that certain linguistic styles can affect the unfolding of conversations. The results confirmed that gender also drives the flow of interaction.…”
Section: Chatbot Designmentioning
confidence: 99%
“…Qiu & Benbast (2009) found that anthropomorphizing bots improves social presence, trust and usage intentions. Ahmad et al (2020) found that certain linguistic styles can affect the unfolding of conversations. The results confirmed that gender also drives the flow of interaction.…”
Section: Chatbot Designmentioning
confidence: 99%
“…For example, one study found that social supportiveness of the CA led to a higher test score (Saerbeck et al, 2010). Three studies reported that CAs with an agreeable, extravert, and caring personality could assist humans better in team performance and learning performance (Ahmad et al, 2020;Hanna & Richards, 2014b;Lee et al, 2007). The remaining study found that CAs having a matched personality with human users could enhance shared understanding of the task (Hanna & Richards, 2015).…”
Section: Relationships Between Antecedents and Outcomes Of Knowledge ...mentioning
confidence: 99%
“…Personality plays an important role in building and maintaining interpersonal relationships [106,107], as well as human-agent [52,108] relationships. Agent personalities are typically created by simulations of human personalities through neural networks [109][110][111] and then expressed via visual appearance, voice, or behavioral cues such as facial expression, gesture, or interaction styles [112]. Conversational agents can be designed in such a way that their personalities align with an organization's image, which would be distinct for a financial institution or service as opposed to other contexts such as commerce or transport [113].…”
Section: Technologies For Agent Embodimentmentioning
confidence: 99%